Handphone XXX: Video 3GP dan Moralitas - Anzieb Anzieb (Antropologi Indonesia, 2012)
This article examines the development of cell phone technology in relation to the cultural practices, in particular the practice of making 3GP sex videos and how public responses to the spread of such video into the public domain. People who recorded their sexual activities mostly admitted that they did it spontaneously or just for fun. The majority of people who recorded their sexual activities aimed not to distribute the video. In addition, those recordings are generally not meant for commercial use, which differentiate them from porn movies. For both men and women making a 3GP video brings unique sensations and new experiences with it. Furthermore, 3GP video can be creative experiment that involves bodies and technology, a way of self-knowledge and self-reflection, and an expression of affection. Public reaction to 3GP video files which widely spread is usually negative. These videos were considered violating moral values as well as criminal acts. Most accusations are directed to the young people which allegedly having moral decadence and misused the technology. Injustice is found in the responses and the repressive attitudes given by certain individuals or institutions who feel they have the authority to judge people involved in 3GP video recording. Keywords: cell phone, sexuality, morality, and moral panics